Cost and Income Analysis of Seaweed Cultivation Using the Off-Base Method in Seriwe Village Jerowaru Subdistrict East Lombok District - Muhammad Anwar (Jurnal Ilmiah Membangun Desa dan Pertanian, 2023)
As part of the world's Coral Triangle, Indonesia has economically valuable seaweed (Eucheuma cottoni), and thousands of species worldwide can grow well in Indonesian waters. The research aims to determine the costs and income of offshore seaweed cultivation in Seriwe Village, Jerowaru District. The study uses descriptive methods with data collection techniques through direct interviews. The research conclusion is that the cost of cultivating seaweed is IDR4,762,122 per area of ​​developed land or IDR103,524,391 per hectare, and the income is IDR7,978,878 or IDR173,116,913 per hectare. From a regulatory perspective, all parties should monitor every policy issued by the regional government and provide intensive assistance to cultivators using a group approach by introducing cultivation techniques, innovation, and post-harvest management that have added value.